First Zinc Bromide Promoted Annulative Domino Reactions between Enamines and Cyclic Morita–Baylis–Hillman Alcohols: Synthesis of N,O-Ketals - Bouhalleb, Ghalia; Meddeb, Ahmed; Bourguiba, Noura Fakhar; Legros, Julien; Poli, Giovanni; Rezgui, Farhat (Synlett, 2020)
A new efficient ZnBr2-mediated annulative domino reaction between enamines and cyclic Morita–Baylis–Hillman (MBH) alcohols is disclosed. The process involves a tandem sequence (intermolecular conjugate addition of enamines to MBH alcohols and intramolecular nucleophilic addition of the hydroxyl moiety to the transiently generated iminium ion), affording the corresponding N,O-ketals diastereoselectively in good yields.
Keywords: MBH alcohol; conjugate addition; enamines; domino reactions; zinc bromide; N,O-ketals